Analisis Pengaruh Pajak Hotel, Pajak Restoran Dan Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Subulussalam - Marliana, Marliana; Dhalimunthe, Ahmad Amin; Harahap, Rahmat Daim (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The purpose of this study was to determine the effect of hotel tax, restaurant tax and advertisement tax on local revenue (PAD) of Subulussalam City in 2015-2020. Regional Original Revenue (PAD) is one of the regional revenues obtained through the potential of an area. One of the local revenue comes from hotel tax, restaurant tax and advertisement tax. The data used in this study is secondary data, namely data on hotel tax receipts, restaurant taxes, advertisement taxes and local revenue for 2015-2020 which were obtained from the Office of the Regional Financial Management Agency of Subulussalam City. The statistical mode used in this study is the classical assumption test and hypothesis testing such as multiple linear regression equations, t test and F test. The results of this study indicate that hotel tax has a positive but not significant effect on local revenue because t count (1,134) < t table (4.303), Restaurant Tax has a positive and significant effect on local revenue because t count (4.544) > t table (4.303), advertisement tax has a negative but not significant effect on local revenue because (-2.177) < t table (4.303 ), and simultaneously hotel tax, restaurant tax and advertisement tax have an effect on local revenue.